Impact of pollination and fertilization on sesame production in the reclaimed lands, Ismailia governorate, Egypt - Blal Abd Elfatah H.; Kamel Soliman M.; Mahfouz Hatem M.; El-Wahed Maysa Said Abd (Journal of Agricultural Sciences (Belgrade), 2012)
The research was conducted at the Agriculture Research Farm, Faculty of Agriculture, University of Suez Canal during the sesame growing seasons of 2011 and 2012. For the purpose of studying the impact of insect pollination and nitrogen fertilization on sesame production, the experiment was divided into 13 treatments of open pollination and non open pollination with three different levels of ammonium nitrate (N) and one level of seryalin as bio-fertilizer. Non open pollination treatments were covered before the start of flowering period with a perforated net bag to allow the air to pass through and to prevent insects from approaching the plants. Quantitative and qualitative parameters were measured as follows: number of capsules per plant, capsule weight, number of seeds per capsule, weight of 1000 seeds, germination rate, seedling vigour and oil content. Results clearly demonstrate that qualitative and quantitative parameters of sesame crop significantly increased with open pollination and with the increase of nitrogen fertilizer level up to 95 kg N/ha plus or minus seryalin in reclaimed sandy soils in Ismailia, Egypt.